Diuretics in patients with metabolic disturbances - I. E. Chazova; V. B. Mychka (Кардиоваскулярная терапия и профилактика)
Aim. To study antihypertensive effectiveness of indapamide retard, its effects on carbohydrate, lipid, purine, electrolyte metabolism in patients with mild arterial hypertension (AH) and metabolic syndrome (MS). Material and methods. The study included three phases: initial (screening), 12-week active treatment, and 36-week self-control phase. In total, 619 patients were randomized into two groups. Active treatment group received indapamide retard combined with non4pharmaceutical weight reduction measures; control group received non-pharmaceutical intervention only. At baseline, total cholesterol (CH), low-density lipoprotein CH (LDL-CH), uricacid, potassium, sodium levels were measured; glucose tolerance test was performed. After active treatment phase, all patients receiving indapamide retard and achieving target blood pressure (BP) levels were recommended to continue the treatment under self-control. Individuals failing to achieve target BP levels were recommended to take perindopril in addition. If needed, control group patients were also administered antihypertensive therapy. Results. After 12-week therapy, target BP levels were achieved in 61,8% of patients receiving indapamide retard, and 48,4% participants of control group; after 12 months - in 69,4% and 52,7%, respectively. Body weight significantly reduced in both groups, by 3 kg on average, waist circumference - by 3 cm. Carbohydrate and lipid metabolism parameters also improved: in 37% of active treatment patients and 25,2% of control group individuals glucose tolerance improved, atherogenicity index decreased. Indapamide retard therapy was well tolerated. Conclusion. Indapamide retard demonstrated good antihypertensive effectiveness and beneficial effects on carbohydrate and lipid metabolism in MS patients.